Testing single extraction methods and in vitro tests to assess the geochemical reactivity and human bioaccessibility of silver in urban soils amended with silver nanoparticles. (September 2015) - Cruz, N.; Rodrigues, S.M.; Tavares, D.; Monteiro, R.J.R.; Carvalho, L.; Trindade, T.; Duarte, A.C.; Pereira, E.; Römkens, Paul F.A.M.
Highlights: Methods to assess the oral bioavailability of Ag in soils need further development. Ag is mobilized to a larger extent by in vitro bioaccessibility tests than by dilute HNO3 extraction. Despite low geochemical reactivity, human exposure to Ag in soils can be significant. For Ag, bioaccessibility tests are essential to estimate potential risks for humans. Abstract: To assess if the geochemical reactivity and human bioaccessibility of silver nanoparticles (AgNPs) in soils can be determined by routine soil tests commonly applied to other metals in soil, colloidal Ag was introduced to five pots containing urban soils (equivalent to 6.8 mg Ag kg −1 soil). Following a 45 days stabilization period, the geochemical reactivity was determined by extraction using 0.43 M and 2 M HNO3 . The bioaccessibility of AgNPs was evaluated using the Simplified Bioaccessibility Extraction Test (SBET) the "Unified BARGE Method" (UBM), and two simulated lung fluids (modified Gamble's solution (MGS) and artificial lysosomal fluid (ALF)). The amount of Ag extracted by 0.43 M and 2 M HNO3 soil tests was <8% and <50%, respectively of the total amount of Ag added to soils suggesting that the reactivity of Ag present in the soil can be relatively low. The bioaccessibility of Ag as determined by the four in vitro tests ranged from 17% (ALF extraction) to 99% (SBET) indicating that almost all Ag can be released from soil due to specific interactions with the organic ligands present in the simulated body fluids. This study shows that to develop sound soil risk evaluations regarding soil contamination with AgNPs, aspects of Ag biochemistry need to be considered, particularly when linking commonly applied soil tests to human risk assessment.